Resolução de alteração estéticaem dente anterior com projeção cervical de esmalte - Suzuki, Thaís Yumi Umeda; Kina, Eunice Fumico Umeda; Kaminagakura, Shigueru; Kina, José Ricardo [UNESP] (My University, 2013)
Enamel projection is often localized in furcation area between the roots of molars and is considered as predisposing factor for localized periodontal disease. When localized in anterior teeth, may determine anti-aesthetic condition as gingival recession. In this case, an enamel projection in tooth 23 produce an anti-aesthetic condition with was treated by mucogingival surgery.

As projeções de esmalte são mais prevalentes nas áreas de furca de dentes posteriores, e são consideradas como fatores predisponentes para o início da doença periodontal localizada. Quando em dentes anteriores, podem determinar alterações estéticas semelhantes às recessões gengivais. Neste caso clínico, relatou-se a resolução de uma projeção de esmalte em um dente anterior com alto comprometimento estético, através da aplicação de cirurgia mucogengival.
Resolution of the aesthetic alteration in anterior tooth with cervical enamel projection
Keywords: Enamel projection; Mucogingival surgery; Esthetic; Gingival recession; Projeção de esmalte; Cirurgia mucogengival; Estética; Recessão gengival